Effects of plant density and nitrogen rate on cotton yield and nitrogen use in cotton stubble retaining fields - Shi-hong WANG; Li-li MAO; Jia-liang SHI; Jun-jun NIE; Xian-liang SONG; Xue-zhen SUN (Journal of Integrative Agriculture, 2021)
Increasing nitrogen (N) rate could accelerate the decomposition of crop residues, and then improve crop yield by increasing N availability of soil and N uptake of crops. However, it is not clear whether N rate and plant density should be modified after a long period of cotton stubble return with high N rate. This study seeks to assess the effects of N rate and plant density on cotton yield, N use efficiency, leaf senescence, soil inorganic N, and apparent N balance in cotton stubble return fields in Liaocheng, China, in 2016 and 2017. Three plant densities 5.25 (D5.25), 6.75 (D6.75) and 8.25 (D8.25) plants m−2 and five N rates 0 (N0), 105 (N105), 210 (N210), 315 (N315), and 420 (N420) kg ha−1 were investigated. Compared to the combination used by local farmers (D5.25N315), a 33.3% N reduction and a 28.6% increase in plant density (D6.75N210) can maintain high cotton yield, while a 66.7% N reduction at 6.75 plants m−2 (D6.75N105) can only achieve high yield in the first year. Biological yield increased with the increase of N rate and plant density, and the highest yield was obtained under 420 kg N ha−1 at 8.25 plants m−2 (D8.25N420) across the two years under investigation. Compared to D5.25N315, N agronomic efficiency (NAE) and N recovery efficiency (NRE) in D6.75N210 increased by 30.2 and 54.1%, respectively, and NAE and NRE in D6.75N105 increased by 104.8 and 88.1%, respectively. Soil inorganic N decreased sharply under 105 kg N ha−1, but no change was found under 210 kg N ha−1 at 6.75 plants m−2. N deficit occurred under 105 kg N ha−1, but it did not occurr under 210 kg N ha−1 at 6.75 plants m−2. Net photosynthetic rate and N concentration of leaves under N rate ranging from 210 to 420 kg ha−1 were higher than those under N rate of 0 or 105 kg N ha−1 at all three densities. The findings suggest that D6.75N210 is a superior combination in cotton stubble retaining fields in the Yellow River Valley and other areas with similar ecologies.